INTEGRATING STEAM-Tri N APPROACHES IN SCIENCE EDUCATION: EXPLORING THE USE OF PAPER PULP BASED DIGESTIVE TORSO MODELS TO FOSTER STUDENT CREATIVITY - Ardi, Muhammad Ilmi; Zulfiati, Heri Maria; Nisa, Ana Fitrotun; Barriyah, Insanul Qisti (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2025)
This study examines the effectiveness of paper pulp-based digestive organ torso props with the STEAM-Tri N approach in enhancing elementary school students' creativity. The problem stems from the need for interdisciplinary learning methods that stimulate creative thinking through hands-on activities. Using descriptive qualitative methodology with an explorative approach, the research involved 20 fifth-grade students at SDN 3 Jogosetran, Kalikotes District, Klaten Regency in the 2024/2025 academic year. Data collection was conducted through observation, interviews, and documentation. The results showed a significant improvement in creativity with 80% of students successfully achieving Creative and Very Creative categories, while only 5% remained in the Less Creative category. The integration of the STEAM approach with the Tri-N learning model (Niteni, Nirokke, Nambahi) successfully created an engaging project-based learning environment, activating students' divergent thinking, innovation, independence, and collaborative skills through the digestive system props creation process. In conclusion, this pedagogical approach effectively transforms traditional learning into an active, creative experience, significantly contributing to developing students' comprehensive understanding and skills in the context of 21st-century education requirements.